2015
DOI: 10.1128/iai.02863-14
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ferroportin-1 Expression and Rapid Splenic Iron Loss Occur with Anemia Caused by Salmonella enterica Serovar Typhimurium Infection in Mice

Abstract: e The Gram-negative intracellular bacterium Salmonella enterica serovar Typhimurium causes persistent systemic inflammatory disease in immunocompetent mice. Following oral inoculation with S. Typhimurium, mice develop a hematopathological syndrome akin to typhoid fever with splenomegaly, microcytic anemia, extramedullary erythropoiesis, and increased hemophagocytic macrophages in the bone marrow, liver, and spleen. Additionally, there is marked loss of iron from the spleen, an unanticipated result, given the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
(97 reference statements)
1
16
1
Order By: Relevance
“…This alteration per se may explain the liver iron retention and the decrease in serum iron levels observed in infected mice. Our data are in apparent contrast with previously reported observations of an increase in ferroportin expression associated with Salmonella infection (32,33). These discrepancies may be explained by two main reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…This alteration per se may explain the liver iron retention and the decrease in serum iron levels observed in infected mice. Our data are in apparent contrast with previously reported observations of an increase in ferroportin expression associated with Salmonella infection (32,33). These discrepancies may be explained by two main reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…However, countervailing effects may predominate during chronic infection: mechanisms that increase ferroportin transcription appear as a part of a natural and protective iron-modulating innate immune response to Salmonella infection of macrophages, and this response can be enhanced by interferon-gamma (Nairz et al, 2008). This increased expression of ferroportin in macrophages is also observed in vivo following infection of mice, where it results in loss of spleen iron (Brown et al, 2015). The upregulation of ferroportin in Salmonella -infected macrophages is at least in part driven by nitric-oxide-mediated Nrf2 activation, which in turn increases transcription of the ferroportin gene (Nairz et al, 2013).…”
Section: Ferroportin and Infectionmentioning
confidence: 79%
“…Previous studies in this model also revealed local mechanisms in macrophages that limit iron availability, including induction of ferroportin transcription by interferon γ, nitric oxide and nuclear factor erythroid 2-related factor 2 (NRF2) [40]. This may help explain the reduced spleen iron levels seen in more chronic Salmonella typhimurium infection [41]. More work is needed to better understand the diverse roles of hepcidin and iron in infection and immunity, and the reader is referred to recent reviews for more in depth discussions [7;40].…”
Section: Hepcidin and The Pathogenesis Of Aimentioning
confidence: 90%